Analysis of coronavirus envelope protein with cellular automata model. Issue 6 (2nd November 2022) - Hazari, Raju; Pal Chaudhuri, Parimal
Abstract : The reason of significantly higher transmissibility of SARS Covid (2019 CoV-2) compared with SARS Covid (2003 CoV) and MERS Covid (2012 MERS) can be attributed to mutations reported in structural proteins, and the role played by non-structural proteins (nsps) and accessory proteins (ORFs) for viral replication, assembly, and shedding. Envelope protein E is one of the four structural proteins of minimum length. Recent studies have confirmed critical role played by the envelope protein in the viral life cycle including assembly of virion exported from infected cell for its transmission. However, the determinants of the highly complex viral–host interactions of envelope protein, particularly with host Golgi complex, have not been adequately characterized. CoV-2 and CoV Envelope proteins of length 75 and 76 amino acids (AAs) differ in four AA locations. The additional AA Gly (G) at location 70 makes CoV length 76. The AA pair EG at locations 69–70 of CoV in place of amino acid R in location 69 of CoV-2, has been identified as a major determining factor in the current investigation. This paper concentrates on the analysis of envelope proteins of SARS covid and MERS covid based on Cellular Automata enhanced Machine Learning (CAML) model developed for study of biological strings. This computational model compares deviation of structure–function of CoV-2 from that of CoV employing CAML model parameters derived out of CA evolution of AA chains of envelope proteins. We hypothesize that large differences of CAML model parameter of CoV-2 and CoV characterize the deviation in structure and function of envelope proteins in respect of interaction of virus with host Golgi complex. This difference gets reflected in the contribution of envelope protein towards overall large difference of transmissibility of CoV-2 and CoV. The hypothesis has been validated from single-point mutational study on- (i) human HBB beta-globin hemoglobin protein associated with sickle cell anemia, (ii) mutants of envelope protein of COVID-2-infected patients reported in recent publications. GRAPHICAL ABSTRACT: UF0001